Mort et disparition durant la dernière dictature militaire argentine (1976-1983) : les « disparus » et les soldats tombés lors de la Guerre des Malouines - Panizo, Laura Marina (2017)
In this paper I summarize the results of my research on violent death and the absence of the body in relation to the last military dictatorship in Argentina, which includes not only the victims of state repression but also those killed in the Malvinas´ War. To this end I worked with two organizations of relatives, "Familiares de Desaparecidos y detenidos por razones políticas" and "Familiares de Caídos en la Guerra de Malvinas e Islas del Atlántico Sur". We will show how relatives joined groups after the death and disappearance of their loved ones, establishing interpretive frameworks to make sense of violent death and bear the losses. These interpretive frameworks show strong feedback with everyday practices and beliefs about death, where specific bonds between the dead and the living are built.